A cross-cultural survey to identify Seniors’ preferences towards the Empathic Virtual Coach - Cuciniello, Marialucia; Amorese, Terry; Greco, Claudia; Raimo, Gennaro; Cordasco, Gennaro; Kornes, Maria Stylianou; Torp Johansen, Anna; Gjellesvik, Kristin Beck; Fernandez, Anais; Kyslitska, Daria; González-Fraile, Eduardo; Fernández-Ruanova, Begoña; et al. (Proceedings of the 2022 IEEE International Conference on Dependable, Autonomic and Secure Computing, International Conference on Pervasive Intelligence and Computing, International Conference on Cloud and Big Data Computing, International Conference on Cyber Science and Technology Congress, DASC/PiCom/CBDCom/CyberSciTech 2022, 2023)
The present investigation is part of the EMPATHIC project aiming at develop an Empathic Virtual Coach (VC) able to promote seniors' healthy lifestyle and independent aging. To this end, it is fundamental to investigate users' preferences towards the implemented automatic system refined on the basis of users' preferences derived from previous field trials with Wizard of Oz (WoZ) experimental sessions. Data collection has been carried out involving three different countries (France, Norway and Spain) and a total of 71 volunteers was enrolled in the planned field trials. Five Virtual Agents (VAs) named Natalie, Alice, Lena, Christian and Adam were purposely designed and users' preferences were assessed using the shortened version of the Virtual Agent Acceptance Questionnaire (VAAQ). This specific tool, developed by members of the EMPATHIC project, includes 7 different sections, and the present work aims to disseminate results of four of the seven sections administered to participants, devoted at assessing respectively: users' willingness to interact (section II); pragmatic, hedonic (Identity and Feeling) and attractiveness qualities (section III); the type of task participants entrusted to the proposed agents among healthcare, housework, protection/security, and front office jobs (section V) and agents voice' quality (section VI). Results reveal seniors' appreciation of agents' pleasantness, originality, voice' quality and ability to engage users in a long lasting interaction with them.
Keywords: assistive technologies; users' acceptance; virtual coach; Scopus(2); WOS(2)